2022
DOI: 10.3389/fphys.2021.797574
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Exercise Programs on Neuregulin 4, Body Composition and Cardiometabolic Risk Factors in Men With Obesity

Abstract: BackgroundNeuregulin 4 (Nrg4) is an adipokine that is sensitive to energy expenditure and with a potential role in metabolic homeostasis and obesity. This study examined the effects of 12 weeks of three different exercise training protocols on Nrg4 levels, cardiometabolic risk factors, and body composition parameters in men with obesity.MethodsSixty adult men with obesity (Mean ± SD; age: 27.60 ± 8.4 yrs.; height: 168.4 ± 2.6 cm; weight: 96.7 ± 7.2 kg) were randomly allocated into four equal (n = 15) groups: H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…S3A, see Supplemental Digital Content, Contour-enhanced funnel plot for overall effects on whole-body lean mass and after adjustment omitting studies which the confidence intervals did not overlap the estimated pooled effects, http://links.lww.com/MSS/ C700). A significant increase of 0.8 kg (95% CI = 0.6 to 0.9 kg, P < 0.001) was observed after omitting five studies (28,52,56,64,103) in which the confidence intervals did not overlap the estimated pooled effect (Fig. 3B).…”
Section: Whole-body Lean Massmentioning
confidence: 94%
“…S3A, see Supplemental Digital Content, Contour-enhanced funnel plot for overall effects on whole-body lean mass and after adjustment omitting studies which the confidence intervals did not overlap the estimated pooled effects, http://links.lww.com/MSS/ C700). A significant increase of 0.8 kg (95% CI = 0.6 to 0.9 kg, P < 0.001) was observed after omitting five studies (28,52,56,64,103) in which the confidence intervals did not overlap the estimated pooled effect (Fig. 3B).…”
Section: Whole-body Lean Massmentioning
confidence: 94%
“…What is more, the increase was greater in HIIT and CRT compared with the MICT. 87 After 24 weeks, metformin therapy resulted in a significant increase of NRG4 levels compared with the baseline and the placebo group. 88 …”
Section: Anti-inflammatory Adipokinesmentioning
confidence: 91%
“…What is more, the increase was greater in HIIT and CRT compared with the MICT. 87 After 24 weeks, metformin therapy resulted in a significant increase of NRG4 levels compared with the baseline and the placebo group. 88 The phenotype of mice with either a gain or loss of NRG4 function suggest that reduced NRG4 may be causally linked to obesity-related impaired glucose metabolism.…”
Section: Clinical Studiesmentioning
confidence: 91%
“…Physical activity is a well-recognized lifestyle intervention to combat obesity (Oppert et al, 2021). Nrg4 levels in men with obesity were significantly increased by 12 weeks of resistance (Saeidi et al, 2021). The results showed that all three modalities increased serum Nrg4 levels and showed favorable metabolic regulatory effects, while the HIIT and CRT programs exerted greater effects on Nrg4 and metabolic risk factors than the MICT program (Saeidi et al, 2021).…”
Section: Nrg4 and Obesitymentioning
confidence: 99%
“…Another study examined the effects of three different training modalities, high-intensity interval training (HIIT), circuit resistance training (CRT), and moderate-intensity continuous training (MICT), on serum Nrg4 levels and various metabolic-related parameters in men with obesity. Increased Nrg4 levels were significantly associated with improved serum glycolipid metabolism markers ( Saeidi et al, 2021 ). The results showed that all three modalities increased serum Nrg4 levels and showed favorable metabolic regulatory effects, while the HIIT and CRT programs exerted greater effects on Nrg4 and metabolic risk factors than the MICT program ( Saeidi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%